A year in the life of ancient Egypt - David, A. Rosalie (Ann Rosalie) (Pen & Sword Archaeology, 2015)
Based on years of prestigious academic work, Professor Rosalie David cleverly presents every aspect of life in ancient Egypt through the lives of various characters, all based on mummies from the Manchester Museum whom Professor Rosalie David has led the study of. Characters hail from all walks of life, including royalty, nobles, officials, craftsmen and peasants, allowing us an insight into absolutely every aspect of everyday, ritual and religious life in ancient Egypt.